Predictors of loneliness among portuguese youths from returned migrant families - Félix Neto (2016)
This investigation approaches the levels and the predictors of loneliness among migrant youths from returned migrant families from France to Portugal. Three research questions guided the study: (1) Does loneliness of migrant youths differ from those who have never migrated? (2) Are migrant youths re-acculturation factors related to their loneliness? (3) Is the adaptation of migrant youths linked to their loneliness? The answer to these questions is important to improve migrant youths re-acculturation experiences and their adaptation. The sample included 222 youths from returned migrant families from France. Participants completed the brief Portuguese version of the Revised UCLA Loneliness Scale (ULS-6), in addition to measures of re-acculturation and adaptation. A control group comprised of 211 Portuguese adolescents who have never migrated was also involved in the investigation. Youths from returned migrant families showed lower levels of loneliness than their native Portuguese counterparts who have never migrated. Demographic, re-acculturation, and adaptation factors were significantly related to adolescents loneliness. Major predictors of loneliness were age at return, contacts with peers without migratory experience, perceived discrimination, stressful adaptation experience, and satisfaction with life. © 2015 Springer Science+Business Media Dordrecht